Phosphine-catalyzed vinylation at low acetylene pressure - Sitte, Nikolai A.; Menche, Maximilian; Tužina, Pavel; Bienewald, Frank; Schäfer, Ansgar; Comba, Peter; Rominger, Frank; Hashmi, A. Stephen K.; Schaub, Thomas (The journal of organic chemistry, 2021)
The vinylation of various nucleophiles with acetylene at a maximum pressure of 1.5 bar is achieved by organocatalysis with easily accessible phosphines like tri-nbutylphosphine. A detailed mechanistic investigation by quantum-chemical and experimental methods supports a nucleophilic activation of acetylene by the phosphine catalyst. At 140 °C and typically 5 mol % catalyst loading, cyclic amides, oxazolidinones, ureas, unsaturated cyclic amines, and alcohols were successfully vinylated. Furthermore, the in situ generation of a vinyl phosphonium species can also be utilized in Wittig-type functionalization of aldehydes.
Gesehen am 15.11.2021